Study of Physical Properties of Nano-Silica Coated Cotton Textiles - Sidra Saleemi; Farooq Ahmed; Samandar Malik (Mehran University Research Journal of Engineering and Technology, 2015)
This research was aimed to investigate the effect of silica sol-gel coating on air permeability, stiffness and tensile properties of dyed cotton fabric. Various concentrations of silica nanoparticles were applied on dyed cotton substrate using two different cross-linkers through sol-gel method. The homogenous sol-gel coating dispersions were prepared by using an ultrasonicator. Coated samples were tested for mechanical and comfort properties such as tensile strength, stiffness, crease recovery and air permeability. It was found that tensile strength and crease recovery of coated substrate were slightly improved. On other hand, it was observed that fabric stiffness and air permeability were affected slightly by increasing concentration of silica nano particle. It was also observed that type of cross-linker has strong influence on coated fabric?s strength and flexural rigidity.